The Influence of Celebrity Endorsers and Product Reviews on Fashion Product Purchase Decisions on E-Commerce Shopee on FKIP UNS Students - Istiqomah, Oktavia Putri; Octoria, Dini (FKIP Universitas Lampung, 2024)
The world is increasingly developing in various fields, one of which is the field of Economics with the presence of E-Commerce. The large number of E-Commerce users has given rise to many efforts by business actors, including product reviews and celebrity endorsers. This study aimed to determine two things: (1) the influence of celebrity endorsers on the decisions of FKIP UNS students to buy fashion items on Shopee e-commerce and (2) the impact of product reviews on the same student decisions. (3) The influence of product reviews and celebrity endorsers on the decisions of FKIP UNS students to buy fashion items on Shopee. This research employs a quantitative methodology. The participants in this study were current students in the 2020–2022 class at Sebelas Maret University's Faculty of Teacher Training and Education. With a sample of 376 respondents, proportionate random sampling with probability sampling was the sample strategy employed. A Likert scale-equipped questionnaire that was disseminated using Google Forms was employed as the data collecting tool. Using SPSS 25 software, simple and multiple linear regression analysis was performed on the data. The study's findings resulted in the following conclusions: (1) The use of celebrity endorsers positively and significantly influences students' decisions in buying fashion products on Shopee e-commerce, and (2) Students' decisions in using product reviews also have a positive and significant impact. Students (3) Students' decisions in buying fashion items on Shopee e-commerce are positively and significantly influenced by product reviews and celebrity endorsers.Keywords: Celebrity Endorser, Product Reviews, Purchase DecisionsDOI: http://dx.doi.org/10.23960/E3J/v7i1.94-102